Community Collective Engagement: Developing a Decision Model to Increase Intention in Early Detection of Cervical Cancer - Sodang Sidabutar; Tatin Wahyanto; Yunardi Yunardi; Peterson Yosua Silaen (International Journal Of Health Science, 2026)
Early detection of cervical cancer is crucial in reducing mortality from this disease. Despite widespread health education, community participation in screening remains low, primarily due to stigma and social taboos. Aim: This study aims to develop a decision-making model based on women's collective involvement in Posyandu (Integrated Health Post) to increase their intention to undergo early cervical cancer screening. Methods: Using a mixed-methods approach, this study involved 200 respondents from various Posyandus within the Community Health Center coverage area. The model was developed through three stages: Formulation of a basic conceptual framework, Development of a measurement strategy, and Validation through surveys and in-depth interviews. Data analysis was conducted using Confirmatory Factor Analysis (CFA) and Structural Equation Modeling (SEM) with the assistance of AMOS software. Results: The results indicate that collective involvement has a significant influence on intention, and the developed model demonstrated good statistical fit. Conclusion: This study contributes to the development of engagement theory in a community context and provides strategic recommendations for improving community well-being through early cervical cancer detection.